Lithium ion battery electrolyte and application thereof

By using non-aqueous solvents, lithium salts and specific additives in the lithium-ion battery electrolyte, a rapid lithium-ion migration channel is constructed, which solves the problems of high DC impedance and poor high-temperature cycling performance of lithium-ion batteries in low-temperature environments, and achieves efficient fast charging and long life.

CN119725745AActive Publication Date: 2025-03-28ENVISION DYNAMICS TECH (JIANGSU) CO LTD +1
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411896441.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-28
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

Lithium-ion batteries face problems such as high DC impedance, low lithium-ion transport kinetics, high viscosity, poor wetting, low body phase diffusion ability of positive/negative active materials and poor interface quality of solid electrolytes in low temperature environments, which limit their application.

Method used

Using a lithium-ion battery electrolyte containing a non-aqueous solvent, a lithium salt and a specific additive, a lithium ion rapid migration channel is constructed through the combined use of the first additive and the second additive, reducing the DC impedance, and improving the high-temperature gas production and cycling performance.

Benefits of technology

It effectively reduces the DC impedance of lithium-ion batteries at low temperatures, improves the fast charging rate window, improves the high-temperature circulation capacity retention rate, and improves the fast charging and long life in the phosphate system.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725745A_ABST
    Figure CN119725745A_ABST
Patent Text Reader

Abstract

The invention provides a lithium ion battery electrolyte and application thereof. The electrolyte comprises: a non-aqueous solvent; a lithium salt; the additives comprise a first additive and a second additive, the structural formula of the first additive is a formula A, and the structural formula of the second additive is a formula B; # imgabs0 # R1 is selected from the group consisting of-H,-F,-SiF3, a C1-6 alkyl group and a fluorinated C1-6 alkyl group, a C1-6 alkoxy group and a fluorinated C1-6 alkoxy group, a C2-6 alkenyl group and a fluorinated C2-6 alkenyl group, a C2-6 alkenyloxy group and a fluorinated C2-6 alkenyloxy group, a C2-10 alkynyl group and a fluorinated C2-10 alkynyloxy group, a C3-8 cycloalkyl group and a fluorinated C3-8 cycloalkyl group, a C3-8 alkylene oxide group and a fluorinated C3-8 alkylene oxide group, a C6-12 aryl group and a fluorinated aryl group, a C6-12 heteroaryl group and a fluorinated heteroaryl group, and a carbonyl group; a sulfonyl group, a fluorine-containing sulfonyl group, or a phosphoryl group; x is selected from one of O or S atoms, and n is selected from any natural number from 1 to 4. According to the lithium ion battery electrolyte and the application thereof provided by the invention, the fast-charging high-dynamic electrolyte with a wide temperature range can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of power batteries, and in particular to a lithium-ion battery electrolyte and applications thereof. Background Art

[0002] As lithium-ion batteries are increasingly used in digital cameras, mobile phones, laptops, power tools, and electric vehicles, they are developing towards higher operating voltages, higher energy and power densities. However, the chemical properties of lithium-ion batteries themselves greatly limit their practical applications in specific environments, such as in cold northern environments and in extremely low-temperature external space environments, where they face difficulties in starting, range anxiety, insufficient low-temperature discharge power, and difficulty in charging.

[0003] In low-temperature environments, there are problems such as the electrolyte having low lithium ion transfer kinetics, high viscosity and poor wettability of the electrolyte at low temperatures, very low diffusion capacity of the positive / negative electrode active material phase, and poor quality of the solid electrolyte interface (Solid Electrolyte Interface), which greatly limit the promotion and application of lithium-ion batteries. Summary of the invention

[0004] The present invention proposes a lithium ion battery electrolyte and its application. Through the lithium ion battery electrolyte and its application provided by the present invention, the DC impedance of the lithium ion battery at low temperature can be effectively reduced, a high-kinetic electrolyte with a wide temperature range and fast charging can be obtained, and the high-temperature gas production performance and high-temperature cycle performance of the lithium ion battery can be improved.

[0005] In order to solve the above technical problems, the present invention provides a lithium ion battery electrolyte, comprising at least the following components:

[0006] Non-aqueous solvents;

[0007] lithium salts; and

[0008] Additives, the additives include a first additive and a second additive, the first additive has a structural formula of Formula A, and the second additive has a structural formula of Formula B;

[0009]

[0010] Wherein, R1 is selected from any one of -H, -F, -SiF3, C1~6 alkyl and fluorinated C1~6 alkyl, C1~6 alkoxy and fluorinated C1~6 alkoxy, C2~6 alkenyl and fluorinated C2~6 alkenyl, C2~6 alkenyloxy and fluorinated C2~6 alkenyloxy, C2~10 alkynyl and fluorinated C2~10 alkynyl, C2~10 alkynyloxy and fluorinated C2~10 alkynyloxy, C3~8 cycloalkyl and fluorinated C3~8 cycloalkyl, C3~8 epoxyalkyl and fluorinated C3~8 epoxyalkyl, C6~12 aryl and fluorinated aryl, C6~12 heteroaryl and fluorinated heteroaryl, carbonyl, sulfonyl and fluorinated sulfonyl or phosphoryl; X is selected from one of O or S element atoms, and n is selected from any natural number from 1 to 4.

[0011] In one embodiment of the present invention, the first additive is selected from at least one of the following compounds: Compound A1, Compound A2, Compound A3 or Compound A4.

[0012] In one embodiment of the present invention, the second additive is selected from at least one of the following compounds:

[0013] Compound B1, Compound B2, Compound B3, Compound B4 or Compound B5.

[0014] In one embodiment of the present invention, the content of the first additive in the electrolyte is 0.1 wt % to 10 wt %, and the content of the second additive in the electrolyte is 0.1 wt % to 8 wt %.

[0015] In one embodiment of the present invention, the content of the first additive in the electrolyte is 0.5wt% to 5wt%, and the content of the second additive in the electrolyte is 0.4wt% to 5wt%.

[0016] In one embodiment of the present invention, the non-aqueous solvent is selected from one or a combination of ethylene carbonate, propylene carbonate, trifluoromethylpropylene, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, ethyl acetate, methyl acetate, ethyl formate, propyl formate, propyl acetate, methyl propionate, ethyl propionate or propyl propionate.

[0017] In one embodiment of the present invention, the lithium salt includes lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide, the content of the lithium salt in the electrolyte is 8wt% to 20wt%, and the content of the lithium bis(fluorosulfonyl)imide in the electrolyte is 0.2wt% to 5wt%.

[0018] In one embodiment of the present invention, the additive further includes a third additive, and the third additive is selected from at least one of vinylene carbonate, 1,3-propane sultone, 1,3-propylene sultone, 2,4-butane sultone, methylene disulfonate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorophosphate, lithium difluorobisoxalatophosphate or vinyl sulfate.

[0019] The present invention also provides a lithium ion battery, comprising:

[0020] A positive electrode sheet, the positive electrode sheet comprising a positive electrode active material, the positive electrode active material comprising a material having a phosphate structure;

[0021] Negative electrode;

[0022] A diaphragm, disposed between the positive electrode sheet and the negative electrode sheet;

[0023] The electrolyte is selected from the lithium-ion battery electrolyte described above.

[0024] The present invention also provides an electronic device, comprising the lithium-ion battery described above.

[0025] In summary, the present invention proposes a lithium ion battery electrolyte and its application. Through the combined use of the first additive and the second additive, a lithium ion rapid migration channel can be constructed, the liquid range distance can be shortened, the interface concentration polarization can be reduced, etc. The electrolyte with high dissociation lithium salt and low viscosity can effectively reduce the DC impedance of the lithium ion battery at low temperature, reduce the desolvation energy of the system at low temperature, and obtain a high-kinetic electrolyte with a wide temperature range and fast charging. It can significantly reduce the solid-liquid concentration polarization and electrochemical polarization of the electrode interface, greatly improving the fast charging rate window of the lithium ion battery. It can improve the interface film formation, and the formed interface film is conducive to the shuttling of lithium ions across the interface, will not increase the interface transfer impedance, improve the cycle dynamics level, improve the high-temperature gas production performance of the lithium ion battery, and improve the high-temperature cycle capacity retention rate. It can play a unique advantage in the fast charging and long life of the phosphate system. DETAILED DESCRIPTION

[0026] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.

[0027] It should be understood that the present invention can be implemented in different forms and should not be interpreted as limited to the embodiments set forth herein. On the contrary, these embodiments are provided to make the disclosure thorough and complete and to fully convey the scope of the present invention to those skilled in the art.

[0028] The technical scheme of the present invention is further described in detail below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0029] The present invention provides a lithium ion battery electrolyte, comprising at least a non-aqueous solvent, a lithium salt and an additive, wherein the additive comprises a first additive and a second additive, the first additive has a structural formula of formula A, and the second additive has a structural formula of formula B:

[0030] Wherein, R1 is selected from any one of -H, -F, -SiF3, C1~6 alkyl and fluorinated C1~6 alkyl, C1~6 alkoxy and fluorinated C1~6 alkoxy, C2~6 alkenyl and fluorinated C2~6 alkenyl, C2~6 alkenyloxy and fluorinated C2~6 alkenyloxy, C2~10 alkynyl and fluorinated C2~10 alkynyl, C2~10 alkynyloxy and fluorinated C2~10 alkynyloxy, C3~8 cycloalkyl and fluorinated C3~8 cycloalkyl, C3~8 epoxyalkyl and fluorinated C3~8 epoxyalkyl, C6~12 aryl and fluorinated aryl, C6~12 heteroaryl and fluorinated heteroaryl, carbonyl, sulfonyl and fluorinated sulfonyl or phosphoryl; X is selected from one of O or S element atoms, and n is selected from any natural number from 1 to 4. Among them, by combining the first additive of highly dissociated lithium salt and the second additive of low viscosity, a rapid migration channel of lithium ions can be constructed, the liquid range distance can be shortened, the interfacial concentration polarization can be reduced, etc. The electrolyte of highly dissociated lithium salt and low viscosity can effectively reduce the direct current resistance (DCR) of lithium-ion batteries at low temperatures, reduce the desolvation energy of the system at low temperatures, and obtain a high-kinetic electrolyte with wide temperature range and fast charging.

[0031] In one embodiment of the present invention, the first additive is selected from any one or a combination of the following compounds:

[0032] Compound A1, Compound A2, Compound A3 or Compound A4, etc. The first additive is an asymmetric lithium salt, which has a low desolvation barrier and can significantly reduce the solid-liquid concentration polarization and electrochemical polarization at the electrode interface, greatly improving the fast charge rate window of lithium-ion batteries.

[0033] In one embodiment of the present invention, the second additive is selected from any one or a combination of the following compounds:

[0034] Compound B1, Compound B2, Compound B3, Compound B4 or Compound B5, etc. The second additive has a lower viscosity and works synergistically with the first additive to have a higher lithium ion migration coefficient, which makes the system have better kinetic performance, can further reduce the interfacial polarization of the system, and improve the high-temperature capacity cycle retention rate of lithium-ion batteries. At the same time, the second additive can improve the interfacial film formation, and the formed interfacial film is conducive to the shuttling of lithium ions across the interface, will not increase the interfacial transfer impedance, improve the cycle kinetics level, improve the high-temperature gas production performance of lithium-ion batteries, and improve the cycle capacity retention rate. It can play a unique advantage in fast charging and long life of phosphate systems.

[0035] In one embodiment of the present invention, the content of the first additive in the electrolyte is 0.1wt% to 10wt%, and for example, 0.5wt% to 5wt%. The content of the second additive in the electrolyte is, for example, 0.1wt% to 8wt%, and for example, 0.4wt% to 5wt%. By controlling the content of the first additive and the second additive, multiple properties of the lithium-ion battery can be taken into account, so that the comprehensive performance of the lithium-ion battery is optimized.

[0036] In one embodiment of the present invention, the additive further includes a third additive, the third additive is selected from at least one of vinylene carbonate (VC), 1,3-propane sultone (PS), 1,3-propylene sultone (PST), 2,4-butane sultone (2,4-Butanesultone), methylene methanedisulfonate (MMDS), lithium difluoro oxalate borate (LiODFB), lithium dioxalate borate (LiBOB), lithium difluorophosphate (LiDFP), lithium difluoro oxalate phosphate (LiDFOP) or vinyl sulfate (1,3,2-Dioxathiolane2,2-dioxide, DTD), and the total content of the third additive in the electrolyte is 0.1wt% to 3wt%. The third additive can cooperate with the first additive and the second additive to further improve the integrity and compactness of the interface film and improve the cycle performance and safety performance of the lithium ion battery.

[0037] In one embodiment of the present invention, the lithium salt is selected from any one or more of lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium tetrafluoroborate (LiBF4), lithium bis(oxalate)borate or lithium difluoro(oxalate)borate, and the content of the lithium salt in the electrolyte is 8wt% to 20wt%, and for example, 10wt% to 15wt%. In one embodiment of the present invention, the lithium salt is selected from lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide, and the content of the lithium bis(fluorosulfonyl)imide in the electrolyte is 0.2wt% to 5wt%, so as to improve the charge and discharge efficiency and energy density of the lithium ion battery, enhance the high and low temperature performance of the battery, and improve the safety performance of the battery.

[0038] In one embodiment of the present invention, the non-aqueous solvent includes, for example, ethylene carbonate (EC), propylene carbonate (PC), trifluoromethyl propylene, ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl acetate (EA), methyl acetate (MA), ethyl formate (MEE), propyl formate (PF), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP) or n-propyl propionate (PP).

[0039] In one embodiment of the present invention, when preparing the electrolyte, in a glove box with an inert gas atmosphere such as argon gas with a moisture content and an oxygen content less than or equal to 0.1 ppm, the non-aqueous solvent is mixed uniformly according to the mass ratio, and the fully dried lithium salt is added to the non-aqueous solvent, and an additive is added to prepare a lithium ion battery electrolyte. The content described in this application is the weight percentage calculated based on the total weight of the electrolyte.

[0040] The present invention proposes a lithium-ion battery, which includes a shell and a bare cell arranged in the shell, and the bare cell includes a positive electrode sheet, a separator and a negative electrode sheet. The separator is placed between the positive / negative electrode sheets to prevent the positive / negative electrode from short-circuiting, so that lithium ions can pass through. The positive electrode sheet, the separator and the negative electrode sheet are stacked in sequence to ensure that a separator is provided between any positive electrode sheet and any negative electrode sheet, and a multi-layer laminate is obtained by winding or folding, and is loaded into a battery shell as a bare cell. Finally, an electrolyte is injected into the shell once or multiple times so that the bare cell is completely immersed in the electrolyte. The electrolyte is, for example, selected from the above-mentioned electrolytes, and plays a role in conducting ions between the positive and negative electrode sheets. In one embodiment of the present invention, the lithium-ion battery is, for example, a secondary battery, and the secondary battery is, for example, a soft-pack battery, a square shell battery or a cylindrical battery, etc. The present invention does not specifically limit the type of lithium-ion battery.

[0041] In an embodiment of the present invention, the positive electrode tab includes a positive electrode current collector and a positive electrode active layer coated on at least one side surface of the positive electrode current collector. Among them, the positive electrode current collector is, for example, a foil formed by surface treatment of nickel, titanium, aluminum, silver, stainless steel, carbon, etc. In addition to the foil, the positive electrode current collector can also be used in any one or a combination of multiple forms such as film, mesh, porous, foam, or non-woven fabric. Among them, the thickness of the positive electrode current collector is, for example, 8 μm to 15 μm. In this embodiment, the positive electrode current collector is, for example, aluminum foil, and the thickness of the aluminum foil is, for example, 13 μm.

[0042] In an embodiment of the present invention, the positive electrode active layer includes a positive electrode active material, a binder, a conductive agent, etc. Among them, the positive electrode active material, for example, includes materials having a phosphate structure, specifically, for example, at least one or more of lithium iron phosphate or lithium manganese iron phosphate, etc., to improve the safety, cycle performance, and temperature adaptability of the lithium-ion battery. Among them, the general formula of lithium manganese iron phosphate is LiMn x Fe 1-x PO4, where the value range of x is 0 < x < 1. The binder is, for example, selected from any one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), ethylene-tetrafluoroethylene copolymer (ETFE), tetrafluoroethylene-hexafluoropropylene-vinylidene fluoride terpolymer (TFE-HFP-VDF), or tetrafluoroethylene-hexafluoropropylene copolymer (FEP), etc. The conductive agent is, for example, selected from any one or more of conductive carbon black (Super P), acetylene black, or Ketjen black, etc. The mass ratio of the positive electrode active material, the conductive agent, and the binder in the positive electrode active layer is, for example, (90 - 97):(1 - 5):(2 - 5).

[0043] In an embodiment of the present invention, the positive electrode active material is, for example, lithium iron phosphate, the binder is, for example, selected from polyvinylidene fluoride, and the conductive agent is, for example, selected from acetylene black. After mixing the positive electrode active material, the conductive agent, and the binder, for example, in a mass ratio of 97:1:2, an organic solvent is added, and the mixture is stirred in a vacuum mixer until the system becomes homogeneous to obtain a positive electrode slurry. Among them, the organic solvent is, for example, selected from N-methylpyrrolidone (NMP). The positive electrode slurry is uniformly coated on the aluminum foil, then dried at room temperature and transferred to an oven for drying. After processes such as cold pressing, edge trimming, slicing, and slitting, a positive electrode tab is obtained. The present application does not limit the preparation method of the positive electrode tab. In other embodiments, the positive electrode tab can also be obtained by any other method of forming a positive electrode tab.

[0044] In one embodiment of the present invention, the negative electrode plate includes, for example, a negative electrode current collector and a negative electrode active layer coated on at least one surface of the negative electrode current collector. The negative electrode current collector is, for example, selected from a copper foil current collector, a composite copper foil current collector, a carbon current collector, a foam copper current collector, or a stainless steel current collector, and the thickness of the negative electrode current collector is, for example, 8 μm to 15 μm. In this embodiment, the negative electrode current collector is, for example, copper foil, and the thickness of the copper foil is, for example, 13 μm.

[0045] In one embodiment of the present invention, the negative electrode active layer includes a negative electrode active material, a conductive agent, a binder and a thickener. Among them, the negative electrode active material includes, for example, any one or more combinations of artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials or lithium titanate. Among them, the silicon-based material includes, for example, one or more of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites or silicon alloys, and the tin-based material includes, for example, one or more of elemental tin, tin oxide compounds or tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries can also be used. These negative electrode active materials can be used alone or in combination of two or more.

[0046] In one embodiment of the present invention, the binder is selected from at least one of styrene butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylic amide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) or carboxymethyl chitosan (CMCS). The thickener includes carboxymethyl cellulose sodium (CMC-Na) and the like, and the conductive agent is selected from any one or more of superconducting carbon, acetylene black, carbon black, ketjen black, carbon dots, carbon nanotubes, graphene or carbon nanofibers and the like. The mass ratio of the negative electrode active material, the conductive agent, the binder, and the thickener in the negative electrode active layer is, for example, (94-97):(1-2):(1-2):(1-2).

[0047] In one embodiment of the present invention, the negative electrode active material is selected from graphite and silicon-carbon composite, and the mass ratio of silicon-carbon composite to graphite is, for example, 2:98 to 5:95. By adding a small amount of silicon-carbon composite, the thickness of the negative electrode active layer can be reduced, the fast charging window of the lithium-ion battery can be improved, and the impact on the first discharge capacity can be reduced. The conductive agent is selected from conductive carbon black, the thickener is selected from sodium carboxymethyl cellulose, and the binder is selected from styrene-butadiene rubber. In one embodiment of the present invention, the negative electrode active material, the conductive agent, the thickener and the binder are mixed, for example, in a mass ratio of 96.5:1:1:1.5, deionized water is added, and the mixture is mixed evenly under the action of a vacuum mixer to obtain a negative electrode slurry, and the negative electrode slurry is coated on a copper foil, and then transferred to an oven for drying after drying at room temperature, and the negative electrode sheet is obtained through cold pressing, trimming, cutting and stripping. In other embodiments, the negative electrode sheet can also be obtained by any other method of forming the negative electrode sheet.

[0048] In one embodiment of the present invention, the diaphragm is, for example, a ceramic diaphragm, a polymer diaphragm, a non-woven fabric or an inorganic-organic composite diaphragm, including but not limited to a single-layer polypropylene film (Polypropylene, PP), a single-layer polyethylene film (Polyethylene, PE), a double-layer PP / PE film, a double-layer PP / PP film and a three-layer PP / PE / PP film, and the thickness of the diaphragm is, for example, 9μm to 15μm.

[0049] In one embodiment of the present invention, the positive electrode sheet, the separator, and the negative electrode sheet are placed in sequence, so that the separator is located between the positive electrode sheet and the negative electrode sheet to play an isolating role, and a bare cell is obtained by winding or stacking. The bare cell is placed in a shell, dried, injected with electrolyte, and sealed, and at least vacuum packaging, standing, forming, and shaping are performed to obtain a lithium-ion battery.

[0050] Hereinafter, the present invention will be explained in more detail by citing examples, which should not be construed as limiting. Appropriate modifications may be made within the scope consistent with the gist of the present invention, all of which fall within the technical scope of the present invention.

[0051] Example 1

[0052] Preparation of electrolyte: In an argon glove box with an oxygen content of 0.1 ppm and a water content of 0.1 ppm, EC: PC: EMC: DMC are mixed in a mass ratio of 25:5:50:20 to obtain a mixed solvent, lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide are added to the mixed solvent to dissolve, and then compound A1 is added and mixed to obtain an electrolyte. In the electrolyte, the content of lithium hexafluorophosphate is 10 wt%, the content of lithium bis(fluorosulfonyl)imide is 3 wt%, and the content of compound A1 is 0.2 wt%.

[0053] Preparation of positive electrode sheet: After lithium iron phosphate, acetylene black and polyvinylidene fluoride are mixed in a mass ratio of 97:1:2, NMP is added, and the system is stirred in a vacuum mixer until the system is uniform to obtain positive electrode slurry. The positive electrode slurry is evenly coated on aluminum foil, and then transferred to an oven for drying after drying at room temperature, and the positive electrode sheet is obtained through cold pressing, trimming, cutting and slitting processes.

[0054] Preparation of negative electrode sheets: The negative electrode active materials are graphite and silicon-carbon composite, and the mass ratio of silicon-carbon composite to graphite is 3:97. The negative electrode active materials, conductive carbon black, sodium carboxymethyl cellulose and styrene-butadiene rubber are mixed in a mass ratio of 96.5:1:1:1.5, deionized water is added, and the mixture is mixed evenly under the action of a vacuum mixer to obtain a negative electrode slurry. The negative electrode slurry is coated on a copper foil, and then dried at room temperature and transferred to an oven for drying. After cold pressing, trimming, cutting and slitting processes, a negative electrode sheet is obtained.

[0055] Selection of diaphragm: Polyethylene with a thickness of 9 μm is used as the base membrane.

[0056] Preparation of battery: stack the positive electrode sheet, separator and negative electrode sheet in sequence, and wind them so that the separator is in the middle of the positive electrode sheet and the negative electrode sheet to play an isolating role, and then obtain a bare battery cell. Then put the bare battery cell into an aluminum plastic film, dry it, inject electrolyte and seal it, and at least go through vacuum packaging, standing, formation and shaping processes to obtain a lithium-ion battery.

[0057] Example 2

[0058] In the electrolyte, the content of compound A1 is 0.5 wt %, and the other steps are consistent with Example 1.

[0059] Example 3

[0060] In the electrolyte, the content of compound A1 is 1 wt %, and the other steps are consistent with Example 1.

[0061] Example 4

[0062] In the electrolyte, the content of compound A1 is 5 wt %, and the other steps are consistent with Example 1.

[0063] Example 5

[0064] In the electrolyte, the content of compound A1 is 5 wt %, and compound B1 is added at the same time, and the content of compound B1 is 0.5 wt %. Other steps are consistent with Example 1.

[0065] Example 6

[0066] In the electrolyte, the content of compound A1 is 5wt%, and compound B1 is added at the same time, and the content of compound B1 is 3wt%. Other steps are consistent with Example 1.

[0067] Example 7

[0068] In the electrolyte, the content of compound A1 is 5wt%, and compound B1 is added at the same time, and the content of compound B1 is 4wt%. Other steps are consistent with Example 1.

[0069] Example 8

[0070] In the electrolyte, the content of compound A1 is 5wt%, and compound B2 and compound B4 are added at the same time, the content of compound B2 is 1.5wt%, and the content of compound B4 is 1.5wt%. Other steps are consistent with Example 1.

[0071] Example 9

[0072] In the electrolyte, the content of compound A1 is 5wt%, and compound B3 and compound B5 are added at the same time, the content of compound B3 is 1.5wt%, and the content of compound B5 is 1.5wt%. Other steps are consistent with Example 1.

[0073] Example 10

[0074] In the electrolyte, the content of compound A1 is 3wt%, and compound B3 and compound B5 are added at the same time, the content of compound B3 is 1.5wt%, and the content of compound B5 is 1.5wt%. Other steps are consistent with Example 1.

[0075] Embodiment 11

[0076] In the electrolyte, the first additives are compound A1 and compound A2, the content of compound A1 is 2wt%, the content of compound A2 is 3wt%, and compound B4 is added at the same time, the content of compound B4 is 3wt%, and the other steps are consistent with Example 1.

[0077] Example 12

[0078] In the electrolyte, the first additives are compound A1 and compound A2, the content of compound A1 is 3wt%, the content of compound A2 is 3wt%, and compound B1 is added at the same time, the content of compound B1 is 3wt%, and the other steps are consistent with Example 1.

[0079] Embodiment 13

[0080] In the electrolyte, the content of compound A1 is 5 wt %, and compound B3 is added at the same time, and the content of compound B3 is 5 wt %. The other steps are consistent with Example 1.

[0081] Embodiment 14

[0082] In the electrolyte, the content of compound A1 is 5wt%, and compound B3 is added at the same time, and the content of compound B3 is 7wt%. Other steps are consistent with Example 1.

[0083] Embodiment 15

[0084] In the electrolyte, the first additive is compound A3, and the content of compound A3 is 5wt%. Compound B2 is added at the same time, and the content of compound B2 is 3wt%. Other steps are consistent with Example 1.

[0085] Example 16

[0086] In the electrolyte, the first additives are compound A1 and compound A3, the content of compound A1 is 3wt%, the content of compound A3 is 2wt%, and compound B3 is added at the same time, the content of compound B3 is 3wt%, and the rest remain unchanged, and the other steps are consistent with Example 1.

[0087] Embodiment 17

[0088] In the electrolyte, the first additives are compound A3 and compound A4, the content of compound A3 is 2wt%, the content of compound A4 is 3wt%, and compound B4 is added at the same time, the content of compound B4 is 3wt%, and the other steps are consistent with Example 1.

[0089] Embodiment 18

[0090] In the electrolyte, the first additives are compound A1 and compound A4, the content of compound A1 is 2wt%, the content of compound A4 is 3wt%, and compound B5 is added at the same time, the content of compound B5 is 3wt%, and the other steps are consistent with Example 1.

[0091] Embodiment 19

[0092] In the electrolyte, the first additives are compound A2 and compound A4, the content of compound A2 is 3wt%, and the content of compound A4 is 2wt%. Compound B2 and compound B5 are added at the same time, the content of compound B2 is 1.5wt%, and the content of compound B5 is 1.5wt%. The other steps are consistent with Example 1.

[0093] Embodiment 20

[0094] In the electrolyte, the first additive is compound A1, compound A3 and compound A4, the content of compound A1 is 2wt%, the content of compound A3 is 2wt%, and the content of compound A4 is 1wt%. At the same time, compound B1, compound B2 and compound B4 are added, the content of compound B1 is 1wt%, the content of compound B2 is 1wt%, and the content of compound B4 is 1wt%. The other steps are consistent with Example 1.

[0095] Embodiment 21

[0096] PS was added to the electrolyte, and the content of PS was 1 wt %. The other steps were consistent with those in Example 6.

[0097] Embodiment 22

[0098] PST was added to the electrolyte, and the content of PST was 1 wt %. The other steps were consistent with those in Example 6.

[0099] Embodiment 23

[0100] LiODFB was added to the electrolyte, and the content of LiODFB was 1 wt %. The other steps were the same as those in Example 6.

[0101] Comparative Example 1

[0102] The first additive and the second additive are not added to the electrolyte, and the other steps are consistent with those in Example 1.

[0103] Comparative Example 2

[0104] VC was added to the electrolyte, and the content of VC was 0.5 wt %. The other steps were the same as those in Comparative Example 1.

[0105] Comparative Example 3

[0106] VC was added to the electrolyte, and the content of VC was 35 wt %. The other steps were the same as those in Comparative Example 1.

[0107] Comparative Example 4

[0108] Compound B1 was added to the electrolyte, and the content of compound B1 was 0.5 wt %. Other steps were consistent with Comparative Example 1.

[0109] Comparative Example 5

[0110] Fluoroethylene carbonate (FEC) was added to the electrolyte, and the content of FEC was 0.5 wt %. Other steps were the same as those in Comparative Example 1.

[0111] In the present invention, in Examples 1-23 and Comparative Examples 1-5, the components of the electrolyte in the lithium ion battery are shown in Table 1, and different electrolytes are used to prepare lithium ion batteries, and the performance of the lithium ion batteries is tested. The test results are shown in Table 2.

[0112] In one embodiment of the present invention, the test method of the low temperature DCR test is as follows: at 25°C, the lithium-ion battery is charged to 3.75V at a constant current of 1 / 3C, and then charged at a constant voltage to a current of 0.05C. Then the battery is discharged to 2.5V at a constant current of 1 / 3C. Repeat the above charging steps once, and the charging capacity is recorded as C0. The battery is discharged to (50%*C0) at a constant current of 1 / 3C. Then the battery is placed at -20°C, and the initial voltage is recorded as U0. The battery is discharged at a constant current of 1C for 30s, and the terminal voltage is recorded as U1. DCR = (U0-U1) / (C0*1).

[0113] In one embodiment of the present invention, the test method of the initial DCR test at room temperature is as follows: at 25°C, the lithium-ion battery is charged to 3.75V at a constant current of 1 / 3C, and then charged to a current of 0.05C at a constant voltage. The battery is then discharged to 2.5V at a constant current of 1 / 3C. Repeat the above charging steps, and after recording the charging capacity as C0, the next charging capacity is recorded as C1. The battery is discharged to (50%*C1) at a constant current of 1 / 3C, and the initial voltage is recorded as U2. The battery is discharged at a constant current of 1C for 30s, and the terminal voltage is recorded as U3. Initial DCR at room temperature = (U2-U3) / (C1*1).

[0114] In one embodiment of the present invention, the test method of the high temperature storage test is as follows: the lithium-ion battery is stored at 60°C for 30 days (30D). The battery is then placed at 25°C and discharged to 2.5V at a constant current of 1 / 3C, and then the battery is charged to 3.75V at a constant current of 1 / 3C, and then charged to a current of 0.05C at a constant voltage. The battery is then discharged to 2.5V at a constant current of 1 / 3C, and the discharge capacity is recorded as C2. The capacity recovery rate is (C2 / C1)*100%. Repeat the above charging steps, and the second charging capacity is recorded as C3. The battery is discharged to (50%*C3) at a constant current of 1 / 3C, and the initial voltage is recorded as U4. The battery is discharged at a constant current of 1C for 30s, and the terminal voltage is recorded as U5. DCR = (U4-U5) / (C3*1). DCR growth rate = (DCR after storage for 30 days-initial DCR) / initial DCR*100%. At the same time, record the volume V1 of the lithium-ion battery at 25°C before storage and the volume V2 at room temperature after storage at 60°C for 30 days. Volume expansion rate = (V2-V1) / V1*100%. In this embodiment, the operating voltage window of the lithium iron phosphate system is 2.5V to 3.75V. In other embodiments, when other positive electrode active materials are selected, the operating voltage window is adjusted according to the positive electrode active materials.

[0115] In one embodiment of the present invention, the test method of the conductivity test is as follows: the electrolyte of the embodiment and the comparative example is prepared and placed in an incubator at 25±0.1°C for 30 minutes, and then the electrolyte is placed in a sample cell, and the Mettler electrode 731-ISM is used to read the data. Each group of tests is tested three times and the average value is taken as the data record.

[0116] In one embodiment of the present invention, the test method of the high temperature cycle test is as follows: the batteries obtained in the embodiment and the comparative example are respectively placed in a 45°C incubator for 120 minutes, and then the charge and discharge cycle test is performed in a 45°C constant temperature box at a charge and discharge rate of 2C / 2C in the range of 2.8 to 3.75V, and the initial discharge capacity of the battery and the discharge capacity after each cycle are recorded. The cycle is repeated for 600 times, and the capacity retention rate = discharge capacity of each cycle / initial discharge capacity of the battery * 100%.

[0117] Table 1. Components and contents of additives in the electrolyte in Examples 1-23 and Comparative Examples 1-5

[0118]

[0119] Table 2. Performance of lithium-ion batteries in Examples 1-23 and Comparative Examples 1-5

[0120]

[0121] Please refer to Table 1 and Table 2. By comparing Examples 1-4 and Comparative Example 1, it can be seen that when the first additive and the second additive are not added to the electrolyte, the conductivity of the electrolyte is low, the low-temperature DCR and room-temperature DCR of the lithium-ion battery are high, the high-temperature storage capacity recovery rate and the high-temperature cycle capacity retention rate are low, and the high-temperature storage volume expansion rate is large, indicating that the performance of the lithium-ion battery is poor. When only the first additive is added to the electrolyte, and as the content of the first additive increases, the higher the conductivity of the electrolyte, the smaller the room-temperature and low-temperature DCR. Since the asymmetric lithium salt desolvation energy barrier is low, the solid-liquid concentration polarization and electrochemical polarization at the electrode interface can be greatly reduced, greatly improving the fast charge rate window of the battery system.

[0122] Please refer to Table 1 and Table 2. It can be seen from the comparison between Examples 4-9 and Comparative Example 4 that when only the second additive is added to the electrolyte, the conductivity of the electrolyte increases slightly, the low-temperature DCR and room-temperature DCR of the lithium-ion battery decrease, and the high-temperature storage volume expansion rate, high-temperature storage capacity recovery rate and high-temperature cycle capacity retention are improved, indicating that only adding the second additive can improve the performance of the lithium-ion battery. Comparing Example 4 and Example 5-9, the interfacial polarization of the system can be further reduced through the synergistic effect of the first additive and the second additive. Compared with the single first additive, the high-temperature capacity cycle retention rate of the lithium-ion battery is higher, and the high-temperature storage gas production is improved. This is because the asymmetric lithium salt and the low-viscosity second additive have a higher lithium ion migration coefficient through synergistic effect, which makes the kinetic performance of the system better. And the second additive can have the ability of interfacial film formation, which has the effect of improving high-temperature gas production compared to the film formation of VC, while not causing excessively high initial interface impedance, and its cycle kinetics is also relatively high.

[0123] Please refer to Table 1 and Table 2. Comparative Examples 5-7 show that when the content of the first additive is fixed and the content of the second additive increases, the conductivity of the electrolyte can be improved, and the high-temperature storage volume expansion rate, high-temperature storage capacity recovery rate and high-temperature cycle capacity remain improved, but the further increase in content reduces the improvement. Therefore, controlling the addition amount of the first additive and the second additive can improve the performance of the lithium-ion battery, while reducing the use of additives and reducing costs. Comparative Examples 8-20 show that the combination of different first additives and second additives can improve the performance of lithium-ion batteries, but the improvement of different performances is slightly different. Therefore, different combinations of first additives and second additives can be selected purposefully according to the purpose of use.

[0124] Please refer to Table 1 and Table 2. By comparing Comparative Examples 2-5, it can be seen that the second additive has the same film-forming ability as VC or FEC. The formed interface film is beneficial to the shuttling of lithium ions across the interface, does not increase the interface transfer impedance, and improves the cycle dynamics. The cycle capacity retention rate is relatively high. The combined use of the first additive and the second additive can exert unique advantages in fast charging and long life of the phosphate system.

[0125] As shown in Table 1 and Table 2, it can be seen from the comparison between Example 6 and Examples 21-23 that when the third additive is PS or PST, the formed interface film is more resilient and has better high temperature stability, and can cooperate with the first additive and the second additive to further improve the high temperature storage performance of the lithium ion battery, but the DCR of the battery will increase slightly. The additive LiDFOB helps to reduce the interface impedance, and the formed interface film has higher ion conductivity, which helps to reduce the interface impedance and improve the discharge capacity.

[0126] The present invention also provides an electronic device, the electronic device includes at least one of the above-mentioned lithium-ion batteries, and the lithium-ion battery is used to provide electrical energy. Among them, the electronic device can be a vehicle, a mobile phone, a portable device, a laptop computer, a ship, a spacecraft, an electric toy and an electric tool, etc. In one embodiment of the present invention, the vehicle is, for example, a new energy vehicle, and the new energy vehicle can be a pure electric vehicle, a hybrid vehicle or an extended-range vehicle, etc. Spacecraft include airplanes, rockets, space shuttles and spacecrafts, etc. Electric toys include fixed or mobile electric toys, such as game consoles, electric car toys, electric ship toys and electric airplane toys, etc. Electric tools include metal cutting electric tools, grinding electric tools, assembly electric tools and railway electric tools, such as electric drills, electric grinders, electric wrenches, electric screwdrivers, electric hammers, impact drills, concrete vibrators and electric planers, etc. The electronic device includes the above-mentioned lithium-ion battery, so the advantages of the above-mentioned lithium-ion battery are included, which will not be elaborated here.

[0127] In summary, the present invention proposes a lithium ion battery electrolyte and its application. Through the combined use of the first additive and the second additive, a lithium ion rapid migration channel can be constructed, the liquid range distance can be shortened, the interface concentration polarization can be reduced, etc. The electrolyte with high dissociation lithium salt and low viscosity can effectively reduce the DC impedance of the lithium ion battery at low temperature, reduce the desolvation energy of the system at low temperature, and obtain a high-kinetic electrolyte with a wide temperature range and fast charging. It can significantly reduce the solid-liquid concentration polarization and electrochemical polarization of the electrode interface, greatly improving the fast charging rate window of the lithium ion battery. It can improve the interface film formation, and the formed interface film is conducive to the shuttling of lithium ions across the interface, will not increase the interface transfer impedance, improve the cycle dynamics level, improve the high-temperature gas production performance of the lithium ion battery, and improve the high-temperature cycle capacity retention rate. It can play a unique advantage in the fast charging and long life of the phosphate system.

[0128] The above description is only a preferred embodiment of the present application and an explanation of the technical principles used. Those skilled in the art should understand that the scope of the invention involved in the present application is not limited to the technical solution formed by a specific combination of the above-mentioned technical features, but should also cover other technical solutions formed by any combination of the above-mentioned technical features or their equivalent features without departing from the inventive concept, such as a technical solution formed by replacing the above-mentioned features with (but not limited to) technical features with similar functions disclosed in this application.

[0129] Except for the technical features described in the specification, the remaining technical features are known technologies to those skilled in the art. In order to highlight the innovative features of the present invention, the remaining technical features will not be described here in detail.

Claims

1. A lithium ion battery electrolyte, characterized in that: At least the following components are included: Non-aqueous solvents; Lithium salts; as well as Additives, the additives include a first additive and a second additive, the first additive has a structural formula of Formula A, and the second additive has a structural formula of Formula B; Wherein, R1 is selected from any one of -H, -F, -SiF3, C1~6 alkyl and fluorinated C1~6 alkyl, C1~6 alkoxy and fluorinated C1~6 alkoxy, C2~6 alkenyl and fluorinated C2~6 alkenyl, C2~6 alkenyloxy and fluorinated C2~6 alkenyloxy, C2~10 alkynyl and fluorinated C2~10 alkynyl, C2~10 alkynyloxy and fluorinated C2~10 alkynyloxy, C3~8 cycloalkyl and fluorinated C3~8 cycloalkyl, C3~8 epoxyalkyl and fluorinated C3~8 epoxyalkyl, C6~12 aryl and fluorinated aryl, C6~12 heteroaryl and fluorinated heteroaryl, carbonyl, sulfonyl and fluorinated sulfonyl or phosphoryl; X is selected from one of O or S element atoms, and n is selected from any natural number from 1 to 4.

2. The lithium ion battery electrolyte according to claim 1, characterized in that: The first additive is selected from at least one of the following compounds:

3. The lithium ion battery electrolyte according to claim 1, characterized in that The second additive is selected from at least one of the following compounds:

4. The lithium ion battery electrolyte according to claim 1, characterized in that: The content of the first additive in the electrolyte is 0.1 wt% to 10 wt%, and the content of the second additive in the electrolyte is 0.1 wt% to 8 wt%.

5. The lithium ion battery electrolyte according to claim 4, characterized in that: The content of the first additive in the electrolyte is 0.5wt% to 5wt%, and the content of the second additive in the electrolyte is 0.4wt% to 5wt%.

6. The lithium ion battery electrolyte according to claim 1, characterized in that: The non-aqueous solvent is selected from one or a combination of ethylene carbonate, propylene carbonate, trifluoromethylpropylene, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, ethyl acetate, methyl acetate, ethyl formate, propyl formate, propyl acetate, methyl propionate, ethyl propionate or propyl propionate.

7. The lithium ion battery electrolyte according to claim 1, characterized in that: The lithium salt comprises lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide. The content of the lithium salt in the electrolyte is 8wt% to 20wt%, and the content of the lithium bis(fluorosulfonyl)imide in the electrolyte is 0.2wt% to 5wt%.

8. The lithium ion battery electrolyte according to claim 1, characterized in that: The additives also include a third additive, which is selected from at least one of vinylene carbonate, 1,3-propane sultone, 1,3-propylene sultone, 2,4-butane sultone, methylene methanedisulfonate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorophosphate, lithium difluorobisoxalatophosphate or vinyl sulfate.

9. A lithium ion battery, characterized in that: include: A positive electrode sheet, the positive electrode sheet comprising a positive electrode active material, the positive electrode active material comprising a material having a phosphate structure; Negative electrode; A diaphragm, disposed between the positive electrode sheet and the negative electrode sheet; An electrolyte, wherein the electrolyte is selected from the lithium-ion battery electrolyte according to any one of claims 1 to 8.

10. An electronic device, characterized in that: Includes the lithium ion battery as claimed in claim 9.

Citation Information

Patent Citations

  • Composite solid electrolyte and solid-stage battery

    CN107887639A

  • Electrolyte and lithium ion battery comprising same

    CN113013487A

  • Lithium ion battery electrolyte additive, non-aqueous electrolyte and lithium ion battery containing electrolyte

    CN115172876A

  • Novel additive for non-aqueous electrolyte and lithium secondary battery comprising same

    CN116711116A

  • Binary asymmetric organic lithium salt, electrolyte and lithium battery

    CN118063359A